O32-1 Digestive cancers and occupational asbestos exposure: significant associations in a french cohort of asbestos plant workers. (1st September 2016) - Boulanger, Mathilde; Morlais, Fabrice; Bouvier, Véronique; Galateau-Sallé, Françoise; Guittet, Lydia; Marquignon, Marie-France; Paris, Christophe; Raffaelli, Claude; Launoy, Guy; Clin, Bénédicte
Abstract : Introduction: Certain digestive cancers, especially colorectal cancer, may be related to asbestos exposure. The aim of our study was to estimate the incidence of digestive cancers within a cohort of asbestos plant workers. Methods: Our study was based on a retrospective cohort of 2, 024 male and female workers occupationally exposed to asbestos, in the Calvados département (France). Data on the cases of digestive cancers were collected thanks to the Calvados' digestive cancer registry. For each localization, the observed number of cancers was calculated from 1st January 1978 to 31st December 2009 and compared with the expected number among the local general population, using Standardised Incidence Ratios (SIR). Asbestos exposure was assessed for each subject, using the company's specific job exposure matrix, and according to three indicators: duration of exposure, Cumulative Exposure Index (CEI), mean atmospheric level. Results: One hundred and nineteen cases of digestive cancers were observed, for an expected number of 77 (SIR = 1.54 [1.28; 1.85]). A significant excess of risk was observed for peritoneal mesothelioma, especially in women (SIR = 43.0 [13.9; 100]). Significantly elevated SIR were also observed among men for: all digestive cancers, even when excluding peritoneal mesothelioma (SIR = 1.50 [1.23; 1.82]); esophageal cancer in general (SIR = 1.67 [1.08; 2.47]) and among those with CEI above 80 fibres/ml.years (SIR = 1.90 [1.16; 2.94]); liver cancer (SIR = 1.85 [1.09; 2.92]). Concerning colorectal cancer, a significant excess of risk was observed for men with exposure duration above 25 years (SIR = 1.75 [1.05; 2.73]). Conclusions: Our results are in favour of a link between long-duration asbestos exposure and colorectal cancer in men, which is consistent with most of the literature. They also suggest a relationship between asbestos exposure and cancer of the oesophagus in men. Finally, there might be an association with small intestine and liver cancers in men.